2023
DOI: 10.20473/ijha.v11i1.2023.67-80
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Patients for Patient Safety: a Qualitative Study on Healthcare Recipients’ Perspectives

Abstract: Background: Patient safety (PS) is a global priority for achieving quality healthcare. Although patient engagement (PE) is a crucial risk-reduction strategy, research on this subject in Indonesia is scarce. Aim: This study aims to explore healthcare recipients’ (HCRs’) perspectives and their potential role in PS. Methods: Exploratory qualitative research was conducted with in-depth interviews (IDIs). This study purposively selected fourteen patients and fifteen caretakers in chronic wards. Content analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…None of the studies reported negative effects on care processes or quality impacts. A study from Indonesia reported the low willingness and readiness of service recipients to engage in patient safety initiatives 231…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies reported negative effects on care processes or quality impacts. A study from Indonesia reported the low willingness and readiness of service recipients to engage in patient safety initiatives 231…”
Section: Resultsmentioning
confidence: 99%